2009
DOI: 10.1021/jp807229c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactant Mixing on Partitioning of Model Hydrophobic Drug, Naproxen, between Aqueous and Micellar Phases

Abstract: Mixed surfactants may improve the performance of surfactant-enhanced solubilization of drugs and thus can serve as the tool for increased bioavalaibility, controlled drug release, and targeted delivery. Solubilization of Naproxen by micellar solutions at 25 degrees C using single and mixed surfactant systems was measured and compared. Solubilization capacity determined with spectrophotometry and tensiometry has been quantified in terms of molar solubilization ratio, micelle-water partition coefficient, and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 69 publications
4
58
0
1
Order By: Relevance
“…Among single ionic surfactant systems, the solubilization is least efficient in SDS as evident from the values of MSR, a possible consequence of electrostatic repulsion between anionic Rutin and negatively charged SDS head groups. Similar results have been reported in solubilization studies of Ibuprofen [53], Sulfanilamide [54] and Naproxen [55]. However, the extent of solubilization is observed to increase with concentration of SDS through hydrophobic interactions due to increase in micelle concentration.…”
Section: Solubilization Of Rutinsupporting
confidence: 87%
“…Among single ionic surfactant systems, the solubilization is least efficient in SDS as evident from the values of MSR, a possible consequence of electrostatic repulsion between anionic Rutin and negatively charged SDS head groups. Similar results have been reported in solubilization studies of Ibuprofen [53], Sulfanilamide [54] and Naproxen [55]. However, the extent of solubilization is observed to increase with concentration of SDS through hydrophobic interactions due to increase in micelle concentration.…”
Section: Solubilization Of Rutinsupporting
confidence: 87%
“…However, at an added dose of CPC above 15,000 mg L −1 , the added P0707 continually decreased the K * d values of o-nitroaniline. As described in equation 1, the decrease of K * d values of o-nitroaniline could be attributed to the forming of mixed micelles in solution, which remains o-nitroaniline in solution by solubilization [26][27][28]. The maximum K * d value of o-nitroaniline is approximately 144 mL g −1 , which is appeared at the added P0707 and CPC dose of 6000 and 10,500 mg L −1 respectively (Fig.…”
Section: Sorption Of O-nitroaniline By Soil In Presence Of the Mixturmentioning
confidence: 87%
“…Giving consideration to the different adsorption mechanisms of cationic and nonionic surfactants on soils and clays, cationic and nonionic surfactants can be expected to adsorb on soils and clays simultaneously without sorptive competition and thus to provide higher organic matter content for sorption. Moreover, in the mixed cationic-nonionic surfactant systems, mixed micelles might form, which may differ significantly from the micelles of individual surfactant and exhibit a number of synergistic advantages over the use of a single surfactant type [26][27][28][29][30][31]. For example, mixed micelles of cationic-nonionic surfactant mixtures may be more effective for partition of organic contaminants than the micelles of individual surfactants [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Especially, the aggregation behaviors and interactions between nonionic surfactant and cationic surfactant have been paid much attention. [3][4][5][6][7][8] Li et al 3 investigated the interaction between the cationic surfactant tetradecyltrimethylammonium bromide (TTAB) and the Pluronic triblock copolymer F127 in water by electromotive force, isothermal titration calorimetry (ITC), differential scanning calorimetry (DSC), and light scattering techniques. They showed that F127 micelles change to mixed F127/TTAB micelles, further to F127/micellar TTAB complex with increasing of TTAB concentration at 35 , and the micellization b ℃ ehavior was emphasized.…”
Section: Introductionmentioning
confidence: 99%